Effect of Recycled Bagasse on Cracking Behavior of Clay Materials - Wenlong Ma; Wenbo Liu; Yuanhang Wang; Binbin Yang (Advances in Materials Science and Engineering)
Bagasse is the residue after juicing sugarcane, and bagasse is a recyclable biological resource that can be used in many ways. Under arid climatic conditions, the clay material shrinks and loses water. Many crisscross drying shrinkage cracks formed on the surface and inside the soil will affect the stability of the soil. In this article, the cracking characteristics of clays with different bagasse contents during the evaporation process have been studied. The cracks were extracted and calculated by digital image processing technology, and the crack characteristics of samples with different bagasse contents were studied by fractal dimension and crack entropy. The results show that when moisture content maintains 34%, the clay material forms only one main crack without bagasse, forms no crack with bagasse content of 9%, and forms a crack network with the bagasse content of 3%. Adding bagasse to the clay can advance the cracking time of the clay, and different contents of bagasse have different effects on the cracking time of the clay. Among these five experimental groups, the clay was affected the most with 3% bagasse content, while the least effect happened with 6% bagasse content. The time can be advanced when the clay crack entropy appears and increases the size of the crack entropy.